2022
DOI: 10.1038/s41562-021-01237-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to affective speech, including motherese, map onto clinical and social eye tracking profiles in toddlers with ASD

Abstract: Motherese is an experience-expectant, human-speci c and innate form of parent speech that enhances social and language learning, and affect and emotion development in infants. An early sign of ASD is the child's lack of responding to motherese and reduced social mother-child interactions. To learn why, we devised a novel experiment quantifying (a) neural responses to motherese and other emotion speech with sleep fMRI and (b) active behavioral preference for motherese with eye tracking in ASD and TD toddlers. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Furthermore, given that normative brain charts indicate that cortical thickness tends to peak in early childhood followed by slow decline over the lifespan 80 , and so, these ASD toddler results combined with others in older ASD samples would indicate that increased early developmental cortical thickening combined with attenuated cortical thinning of LH STC may be a robust and key neural feature of ASD neurodevelopment. Given the observations of early developmental functional abnormalities in LH STC for language 33,34,81 , these converging results may implicate that atypical structural development and underlying genomic mechanisms affecting LH STC 34,35 may perturb the ability of this region to develop functional specialization for processes like language and socialcommunication.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, given that normative brain charts indicate that cortical thickness tends to peak in early childhood followed by slow decline over the lifespan 80 , and so, these ASD toddler results combined with others in older ASD samples would indicate that increased early developmental cortical thickening combined with attenuated cortical thinning of LH STC may be a robust and key neural feature of ASD neurodevelopment. Given the observations of early developmental functional abnormalities in LH STC for language 33,34,81 , these converging results may implicate that atypical structural development and underlying genomic mechanisms affecting LH STC 34,35 may perturb the ability of this region to develop functional specialization for processes like language and socialcommunication.…”
Section: Discussionmentioning
confidence: 96%
“…Our data also suggest that the subgroup of the population with ASD and low attention to motherese may be more homogeneous at some intermediate psychobiological level, thereby potentially justifying the use of this test to stratify the population with autism in future studies of social attention and its correlates. A recent study 27 revealed that toddlers with ASD who showed low attention levels to motherese speech as a group had lower levels of neural functional activity in classic speech-processing areas, such as the superior temporal gyrus, compared with other toddlers with ASD who paid greater attention to motherese speech.…”
Section: Discussionmentioning
confidence: 99%
“…In a brain imaging study, toddlers with ASD who showed the lowest levels of attention to motherese speech also showed the lowest levels of neural functional activation in speech-processing regions and lower language abilities than toddlers who paid greater attention to motherese speech. 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the diagnosis is typically implicitly endowed with a certain type of face validity that most medical diagnoses also possess (e.g., differential biology), many will still assume that the diagnosis should indeed split apart individuals with very different underlying biology behind the phenotype. Evidence has been mounting in recent years suggesting that early language issues are quite important stratifiers, both from a clinical standpoint, but also in terms of underlying biology (3,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). At what point should the field reflect back on whether such changes some several decades back were warranted?…”
Section: Back To the Future -The History Of Autismmentioning
confidence: 99%